INTEGRASI ISLAM DAN SAINS DALAM PERSPEKTIF AL-QUR’AN: RELEVANSI PARADIGMA KEILMUAN AMIN ABDULLAH DI ERA POST-TRUTH - Helga Juliya; Sawaluddin Siregar (Al FAWATIH:Jurnal Kajian Al Quran dan Hadis, 2025)
This article examines the new scientific paradigm offered by M. Amin Abdullah in the context of dialogue between Islam and science in the post-truth era. The background of this research departs from the dichotomy of religious science and general science which results in stagnation in the development of Islamic science in higher education. Through a qualitative approach with the literature study method, this study examines the works and thoughts of M. Amin Abdullah related to the integration-interconnections of knowledge known as the "Spider's Web" model. This concept emphasizes the importance of epistemological dialogue between religious sciences, social sciences, and natural sciences in order to build a holistic, open, and contextual science. The results of the study show that this integrative paradigm is able to bridge the gap between revelation, reason, and empirical reality, and is relevant in facing the challenges of the post-truth era marked by the crisis of truth and polarization of knowledge. Thus, M. Amin Abdullah's ideas offer a new direction for a more inclusive, dynamic, and contemporary reconstruction of Islamic epistemology.